Experiences of moral distress by privately hired companions in Ontario's long-term care facilities. (13th March 2017) - Brassolotto, Julia; Daly, Tamara; Armstrong, Pat; Naidoo, Vishaya
Abstract : Purpose: The purpose of this study was to explore long-term residential care provided by people other than the facilities' employees. Privately hired paid "companions" are effectively invisible in health services research and policy. This research was designed to address this significant gap. There is growing recognition that nursing staff in long-term care (LTC) residential facilities experience moral distress, a phenomenon in which one knows the ethically right action to take, but is systemically constrained from taking it. To date, there has been no discussion of the distressing experiences of companions in LTC facilities. The purpose of this paper is to explore companions' moral distress. Design/methodology/approach: Data were collected using week-long rapid ethnographies in seven LTC facilities in Southern Ontario, Canada. A feminist political economy analytic framework was used in the research design and in the analysis of findings. Findings: Despite the differences in their work tasks and employment conditions, structural barriers can cause moral distress for companions. This mirrors the impacts experienced by nurses that are highlighted in the literature. Though companions are hired in order to fill care gaps in the LTC system, they too struggle with the current system's limitations. The hiring of private companions is not a sustainable or equitable solution to under-staffing and under-funding in Canada's LTC facilities. Originality/value: Recognizing moral distress and its impact on those providing LTC is critical in relation to supporting and protecting vulnerable and precarious care workers and ensuring high-quality care for Canadians in LTC.